2007
DOI: 10.1038/sj.leu.2404763
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory response of human leukemic cells to dsRNA transfection linked to activation of dendritic cells

Abstract: Leukemic cells exert immunosuppressive effects that interfere with dendritic cell (DC) function and hamper effective antileukemic immune responses. Here, we sought to enhance the immunogenicity of leukemic cells by loading them with the double-stranded (ds) RNA Toll-like receptor 3 (TLR3) ligand polyriboinosinic polyribocytidylic acid (poly(I:C)), mimicking viral infection of the tumor cells. Given the responsiveness of DC to TLR ligands, we hypothesized that the uptake of poly(I:C)-loaded leukemic cells by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…As previously described by our group, DCs loaded with apoptotic HSP70-expressing M13 cells and activated by exogenous maturation agents are potent in vitro inducers of mesothelioma-specific CTLs (23). Interestingly, recent studies indicated a relevant adjuvant effect of cellular-associated dsRNA for tumor cells loaded with poly(I:C) (46,47) and for virally Semliki Forest virus-infected Vero cells (48). So, although not directly correlated by our results, we hypothesize that apoptotic mesothelioma cells loaded with viral dsRNA produced by MV infection might be a strong immunogenic signal, leading to the spontaneous maturation of monocyte-derived DCs and the subsequent activation of a relevant MSLN-specific CD8 T-cell response.…”
Section: Cancer Researchmentioning
confidence: 58%
“…As previously described by our group, DCs loaded with apoptotic HSP70-expressing M13 cells and activated by exogenous maturation agents are potent in vitro inducers of mesothelioma-specific CTLs (23). Interestingly, recent studies indicated a relevant adjuvant effect of cellular-associated dsRNA for tumor cells loaded with poly(I:C) (46,47) and for virally Semliki Forest virus-infected Vero cells (48). So, although not directly correlated by our results, we hypothesize that apoptotic mesothelioma cells loaded with viral dsRNA produced by MV infection might be a strong immunogenic signal, leading to the spontaneous maturation of monocyte-derived DCs and the subsequent activation of a relevant MSLN-specific CD8 T-cell response.…”
Section: Cancer Researchmentioning
confidence: 58%
“…We have previously reported that AML cells in response to electroporation with poly(I:C) show improved tumor cell immunogenicity, demonstrated by an enhanced capacity to activate and mature DC [53] and induce the release of NK cell IFN-Îł [78]. Ensuing from these data, in this study, we examined the effect of poly(I:C)-electroporated AML cells on the phagocytic capacity of immature DC and on the cytotoxic function of NK cells.…”
Section: Introductionmentioning
confidence: 91%
“…Poly(I:C) is an agonist of the innate endosomal TLR3 and the cytosolic melanoma differentiation-antigen-5 (mda-5) receptors [47]. It is a well-described danger signal able to trigger cell death and induce the production of proinflammatory cytokines, including type I interferons (IFN), in various cell types [47]–[53]. Under defined conditions, poly(I:C) is a powerful NK cell activation signal [47], [52], [54]–[60] and it has been shown to efficiently activate and mature DC [61]–[66] and stimulate DC-NK cell interactions [55], [67], [68].…”
Section: Introductionmentioning
confidence: 99%
“…For AML, it is not yet clear whether cell lysates or apoptotic cells are preferable for Ag loading onto MoDC [9, 19–25]. Next to enhancing immunogenicity of tumor Ag sources by, for instance, heat shock, addition of DC-maturing stimuli, such as Toll-like receptor ligands (TLR-L), is explored; e.g., electroporation of TLR3-L Poly(I:C) into AML cells results in enhanced uptake of leukemic cells by DC and improves their subsequent maturation and cytokine production [26]. Furthermore, intracellular binding of TLR8 by its ligand R848 has been reported to result in enhanced cross-priming of exogenous Ag by MoDC [27].…”
Section: Introductionmentioning
confidence: 99%